The subnivium, a haven for Trichinella larvae in host carcasses. (April 2019) - Rossi, Luca; Interisano, Maria; Deksne, Gunita; Pozio, Edoardo
Abstract: Parasite nematodes of the genus Trichinella are transmitted from one host to another through the ingestion of larvae present in striated muscles. The longer the survival of muscle larvae in host carcasses, the higher the probability of being ingested by a scavenging host. Thereby, these nematodes developed an anaerobic metabolism favouring their survival in decaying tissues. In addition, muscle larvae of three taxa, namely Trichinella nativa, Trichinella britovi and Trichinella T6, can survive freezing for several months to several years depending on the taxon. The aim of the present work was to investigate the survival time of T. britovi larvae in naturally infected host carcasses preserved beneath or above the snow. Fox and raccoon dog carcasses naturally infected with T. britovi larvae were preserved beneath or above the snow in a cold mountainous area. Temperature and relative humidity were recorded. Every 14 days, muscle samples collected from each carcass, were digested and larvae were counted and given per os to laboratory mice to evaluate their reproductive capacity index (RCI). The RCI of larvae in carcasses preserved beneath the snow (the subnivium) ranged from 23 to 25 at day 0, to 12–18 after 112 days. In contrast, the RCI of larvae in carcasses preserved above the snow ranged from 22 to 27 at day 0, to 0.0 after 112 days. The difference between the RCIs of larvae beneath the snow and above the snow was statistically significant ( P  < 0.01). These data corroborate the hypothesis that the subnivium with its environmental stability favours the survival of Trichinella larvae in host muscles, increasing the probability of their transmission to other hosts. On the other hand, the environment above the snow, characterized by sudden temperature variations, causes strong environmental stress for larvae in host carrions causing their death. Graphical abstract: Image 1 Highlights: The snow cover increases the survival time of Trichinella larvae in host carrions. The subnivium, seasonal refuge of Trichinella larvae in host carcasses. Frequent thermal variations reduce larva survival in host muscles. Muscle putrefaction did not adversely affect the survival of Trichinella larvae.